Using multiple criteria to enter and rank reward design criteria in construction projects - Koochakzadeh, Masoud (2020)
The objective of this study was to The Use of Multi-Criteria Decision Making to Introduce and Rank of Design Criteria of Reward in Construction Projects. In this research, the design criteria of rewards in construction projects are ranked. In the present study, in order to identify and rank the criteria of employee reward allocation the methods of Demetel and expansion of the performance of fuzzy quality in two steps were used. the results showed that the professional ethics is the most important criterion for reward allocation to the employees in the construction projects. Results show that considering the work environment of construction projects, maintaining discipline and having organizational commitment and helping others is very important. Also, having the spirit of teamwork and cooperation with others is very important for working in such environments. One of the notable points in the findings of this study is the less attention paid by construction managers to the use of labor quantity measurement indicators as a criterion for reward allocation and more attention to quality criteria such as professional ethics, creativity, etc., which shows the difference between the nature of the work and the end product of this industry with manufacturing industries such as parts manufacturing.